PERANAN PELAYANAN ADMINISTRASI DALAM MENINGKATKAN PARTISIPASI MASYARAKAT PADA KANTOR LURAH SIRONGO FOLARAHA KECAMATAN TIDORE UTARA KOTA TIDORE KEPULAUAN - Ilfan Baharuddin (Jurnal Akrab Juara, 2019)
This study aims to determine the impact or influence of administration on community participation in development and development in Sirongo Folaraha Subdistrict North Tidore Subdistrict, Tidore Islands City, with the formulation of the problem "whether the role of administrative services can increase community participation in Sirongo Folaraha Village Office North Tidore District Tidore Islands. The method used in this research is descriptive quantitative method with the help of frequency tables. The variables in this study consisted of two variables, namely the independent variable in the form of administrative services and the dependent variable in the form of public participation. To measure the data obtained using indicators related to each of these variables. The data in this study were obtained by conducting observations, interviews, questionnaires and literature studies. To further accentuate the research, in addition to taking samples from the elements of the kelurahan apparatus, they also took samples from the community as a comparison. Research that there is an impact or influence from administrative services by Sirongo Folaraha village officials with community participation in development, this is obtained by looking at the decline in the distribution of respondent data about significant administrative service variables with community participation.